Weak value amplification - new insights and applications (2016)
Three are the main goals of this thesis: To apply the concept of weak value amplification to certain experimental scenarios for detecting tiny changes of certain physical quantities of interust. More specifically, we want to measure extremely small temporal delays between two pulses much longer that the delay to be measured, and explore how far we can go in this direction. To design and implement new devices based on the concept of weak value amplification. We demonstrate a compact and tunable beam displacer that does not make use of beam deflection, and a temperature sensor with enhanced sensitivity based on fiber Bragg gratings technology. To analyze from a fundamental point of view the concept of weak value amplification, to know what it can be done and what it cannot be done. The aim is to reconcile different visions of the technique, and understanding their rationale...-- Tomado de la introducción